TINDAK PIDANA PENGGUNAAN ALAT RAPID TES BEKAS PADA MASA PANDEMI COVID 19 - Tarigan, Tio Pilus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
When this rapid test becomes a travel requirement for prospective passengers, there is a case of using used rapid test kits at Kualanamu International Airport (KNIA). For this reason, it is necessary to study how criminal liability for the crime of using used rapid test kits during the Covid 19 pandemic and what is the role of the police in eradicating the crime of using used rapid test kits during the Covid 19 pandemic. The type of research used in writing this thesis is normative juridical which is descriptive analysis. The data collection technique used is library research.  Criminal liability for the criminal act of using used rapid test kits during the Covid 19 pandemic is contained in a) Article 98 of Law Number 36 of 2009 concerning Health, paragraph (1) and paragraph 3 paragraph (3); b) Article 7 letters a and d of Law No. 8 of 1999 concerning consumer protection; c) Article 196 of Law Number 36 of 2009 concerning Health. The stipulation to hold corporations accountable in the form of accountability of their managers can also be seen in the provisions of Article 46 paragraph (2) of Law Number 7 of 1992: "in the event that the activities referred to in paragraph (1) are carried out by legal entities in the form of limited liability companies, associations, foundations or cooperatives, then the prosecution of the bodies in question is carried out both against those who give orders  to do that act or to act as a leader in that act or to both." The role of the police in eradicating the crime of using used rapid test kits during the Covid 19 pandemic is that the police have succeeded in uncovering the use of used rapid test kits that occurred at Kualanamu International Airport